Thoughts on Cataloging and Classification in a Small Medical Library - Waller, Salvador B. (1970)
This article is based on experience with small library collections. It is an effort to point out some of the problems in cataloging and classification, to arouse an interest in self-analysis on the part of the small library, and to offer some suggestions as to how the small institution can streamline techniques and economize on meager resources with no loss of value to the card catalog. It is recognized that the catalogs in many small libraries are unsuited for their tasks as a result of adhering to philosophies of larger institutions. The small institution has neither the need nor resources for such completeness in cataloging and classification. Deviation from standard rules is not advocated. However, consistency in treatment is advised and adherence in depth to standard rules is questioned.